The conceptual design of a mechatronic system to handle bedridden elderly individuals - Silva, Bruno Manuel Fernandes da (2016)
The ever-growing percentage of elderly people in developed countries have made Ambient Assisted Living (AAL) solutions an important subject to be explored and developed. The increase in geriatric care requests are overburdening specialized institutions that cannot cope with the demand for support. Patients are forced to have to remain at their homes encumbering the spouse or close family members with the caregiver role. This caregiver is not always physically and technically apt to assist the bedridden person with his/her meals and hygiene/bath routine. Consequently, a solution to assist caregivers in these tasks is of the utmost importance. This paper presents an approach for supporting caregivers when moving and repositioning Bedridden Elderly Peoples (BEPs) in home settings by means of a mechatronic system inspired by industrial conveyers. The proposed solution is able to insert itself underneath the patient, due to its low-profile structural properties, and retrieve and reallocate him/her. Ideally, the proposed mechatronic system aims to promote autonomy by reducing handling complexity, alter the role of the caregiver from physically handler of the BEP to an operator/supervisor role, and lessen the amount of effort expended by caregivers and BEPs alike.